2017
DOI: 10.2147/mnm.s107246
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 in the pathophysiology and diagnosis of dry eye syndrome

Abstract: Dry eye and tear dysfunction are common ocular disorders that cause cornea barrier disruption resulting in a poorly lubricated and irregular cornea epithelium, eye irritation and blurred vision. Increased levels and activities of matrix metalloproteinases (MMPs), particularly MMP-9, have been detected in the tears and ocular surface epithelial and inflammatory cells in dry eye. MMPs have been found to participate in disruption of tight junctions in the apical cornea epithelium leading to their accelerated desq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 109 publications
(161 reference statements)
2
25
0
1
Order By: Relevance
“…In the case of MMP9, this enzyme lyses the various components of the corneal epithelial basement membrane and tight junction proteins such as ZO-1 and occludin to maintain corneal epithelial barrier function [ 43 , 44 ]. Increased MMP9 activity in DED is related to a dysfunctional epithelial barrier, increased corneal epithelial erosions, and corneal surface irregularity [ 45 , 46 ] Our findings revealed that PCE inhibited the increase in MMP9 mRNA expression in DED.…”
Section: Discussionmentioning
confidence: 92%
“…In the case of MMP9, this enzyme lyses the various components of the corneal epithelial basement membrane and tight junction proteins such as ZO-1 and occludin to maintain corneal epithelial barrier function [ 43 , 44 ]. Increased MMP9 activity in DED is related to a dysfunctional epithelial barrier, increased corneal epithelial erosions, and corneal surface irregularity [ 45 , 46 ] Our findings revealed that PCE inhibited the increase in MMP9 mRNA expression in DED.…”
Section: Discussionmentioning
confidence: 92%
“…Different from the inflammation factors activated at 4 h, autophagy is a late response to hyperosmotic stress in HCECs at 24 h. After autophagosome formation in HCECs exposed to hyperosmolarity, evidenced by the increases of Beclin1, Atg5, Atg7 and LC3B, as well as the decrease of P62, a few upward blips in cell viability were observed, accompanied by a moderate drawdown of TNF-α, IL-1β, IL-6 as well as IL-8. Autophagy modulates inflammation through influencing the inflammatory cells survival conditions and altering secretion of inflammatory cytokines [ 33 , 44 ], by which autophagy is simultaneously modulated [ 24 ]. Thus, we assessed how modulators of autophagy can relieve ocular surface inflammation linked with dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs participate in the disruption of tight junctions in the apical corneal epithelium leading to their accelerated desquamation and barrier disruption. 67 The role of MMPs in corneal melt, intuitive if one considers the predominance of collagen in the structure of corneal stroma, is well documented. 7,8,57,63,76,87 Specifically for NICM, the study of three cases of diclofenac-induced corneal melt with perforation revealed enhanced expression of MMPs 1 and 9 within corneal epithelial cells, stromal keratocytes, and at the level of the Descemet membrane.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%